Serum and synovial matrix metalloproteinases 1 and 3 in patients with early rheumatoid arthritis: potentially prospective biomarkers of ultrasonographic joint damage and disease activity - Maryam A. Abdelrahman; Hossam M Sakr; Menat A.A Shaaban; Naglaa Afifi (SpringerOpen, 2019)
Background Matrix metalloproteinase-1 (MMP-1) and MMP-3 play important roles in the pathogenesis of rheumatoid arthritis (RA) and have been suggested as markers of disease activity and joint damage. Objective The aim was to analyze the clinical significance of MMP-1 and MMP-3 in relation to markers of disease activity and degree of joint destruction in patients with early RA at presentation and after 6 months. Patients and methods Baseline levels of serum MMP-1 and MMP-3 were assessed in 50 patients with early RA (symptoms <1 year), 20 patients with osteoarthritis (OA), and 20 age-matched and sex-matched healthy controls. Serum MPP-1 and MPP-3 were correlated with disease activity markers [erythrocyte sedimentation rate (ESR), C-reactive protein, disease activity score 28-ESR] and radiographic joint damage using simple erosion narrowing score and musculoskeletal ultrasound of wrist and hand joints. Baseline synovial fluid MMP-1 and MMP-3 levels were evaluated for 20 patients indicated for arthrocentesis. Results Baseline serum MMP-1 and MMP-3 were significantly higher in RA group versus OA group and healthy controls (P<0.001). Synovial MMP-1 and MMP-3 levels were significantly higher in RA versus OA group. Serum MMP-1 and MMP-3 levels significantly correlated with rheumatoid factor titers, anticyclic citrullinated peptide, disease activity score 28-ESR score, joint erosions, and Outcome Measures in Rheumatology score of synovitis and Doppler signals. Serum MMP-1 did not correlate with C-reactive protein, but significantly correlated with the number of erosions at presentation and on follow-up. The number of patients with erosions and the number of erosions per patient increased after 6 months and correlated with serum MMP-1 and MMP-3. The best cutoff values of serum MMP-1 and MMP-3 to discriminate between RA and healthy controls were greater than 20 and greater than 50 ng/ml, respectively. Conclusion Elevated serum levels of MMP-1 and MMP-3 can be used as an indicator of disease activity in patients with early RA and can reflect the degree of joint damage and correlate with the number of new joint erosions.